Endovascular versus medical therapy for large-vessel anterior occlusive stroke presenting with mild symptoms. Issue 3 (April 2020) - Wolman, Dylan N; Marcellus, David G; Lansberg, Maarten G; Albers, Gregory; Guenego, Adrien; Marks, Michael P; Dodd, Robert L; Do, Huy M; Wintermark, Max; Martin, Blake W; Heit, Jeremy J
Background: Acute ischemic stroke patients with a large-vessel occlusion but mild symptoms (NIHSS ≤ 6) pose a treatment dilemma between medical management and endovascular thrombectomy. Aims: To evaluate the differences in clinical outcomes of endovascular thrombectomy-eligible patients with target-mismatch perfusion profiles who undergo either medical management or endovascular thrombectomy. Methods: Forty-seven patients with acute ischemic stroke due to large-vessel occlusion, NIHSS ≤ 6, and a target-mismatch perfusion imaging profile were included. Patients underwent medical management or endovascular thrombectomy following treating neurointerventionalist and neurologist consensus. The primary outcome measure was NIHSS shift. Secondary outcome measures were symptomatic intracranial hemorrhage, in-hospital mortality, and 90-day mRS scores. The primary intention-to-treat and as-treated analyses were compared to determine the impact of crossover patient allocation on study outcome measures. Results: Forty-seven patients were included. Thirty underwent medical management (64%) and 17 underwent endovascular thrombectomy (36%). Three medical management patients underwent endovascular thrombectomy due to early clinical deterioration. Presentation NIHSS ( P  = 0.82), NIHSS shift ( P  = 0.62), and 90-day functional independence (mRS 0–2; P  = 0.25) were similar between groups. Endovascular thrombectomy patients demonstrated an increased overall rate of intracranial hemorrhage (35.3% vs. 10.0%; P  = 0.04), but symptomatic intracranial hemorrhage was similar between groups ( P  = 0.25). In-hospital mortality was similar between groups ( P  = 0.46), though all two deaths in the medical management group occurred among crossover patients. Endovascular thrombectomy patients demonstrated a longer length of stay (7.6 ± 7.2 vs. 4.3 ± 3.9 days; P  = 0.04) and a higher frequency of unfavorable discharge to a skilled-nursing facility ( P  = 0.03) rather than home ( P  = 0.05). Conclusions: Endovascular thrombectomy may pose an unfavorable risk-benefit profile over medical management for endovascular thrombectomy-eligible acute ischemic stroke patients with mild symptoms, which warrants a randomized trial in this subpopulation.